2013
DOI: 10.5935/0103-5053.20130066
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Seized Cocaine Samples by using Chemometric Methods and FTIR Spectroscopy

Abstract: O objetivo deste trabalho foi desenvolver uma metodologia quimiométrica para descrever o perfil químico de amostras de cocaína apreendidas no estado de Minas Gerais (Brasil). A identificação de adulterantes e a quantificação do teor de cocaína foram feitas por cromatografia gasosa acoplada à espectrometria de massa (GC-MS). Espectros de 91 amostras foram obtidos por espectroscopia no infravermelho usando refletância total atenuada (ATR-FTIR), e utilizados na construção de um modelo de análise de componentes pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 0 publications
0
21
1
1
Order By: Relevance
“…Recent studies using this technique for the analysis of cocaine have been presented [10][11][12]. The combination of vibrational spectroscopy and chemometric methods has been considered a promising and simple alternative to extract information directly from the sample.…”
Section: Page 3 Of 47mentioning
confidence: 99%
“…Recent studies using this technique for the analysis of cocaine have been presented [10][11][12]. The combination of vibrational spectroscopy and chemometric methods has been considered a promising and simple alternative to extract information directly from the sample.…”
Section: Page 3 Of 47mentioning
confidence: 99%
“…1,12 Small shifts in peak position and intensity have been observed for the two cocaine forms when the infrared ATR spectra are compared with the transmission mode spectra. 5,17 In ATR spectra, the strong characteristic wavenumber values for the standard cocaine salt sample are 1728, 1712, 1265, 1230, 1105, 1071, 1026, and 729 cm À1 . For standard cocaine base, the peaks are at 1734, 1707, 1273, 1227, 1107, 1068, 1035, and 712 cm À1 (Table 1).…”
Section: Major Peak Assignments Of Cocainementioning
confidence: 99%
“…5 Principal component analysis (PCA) and PLS-DA were utilized for the classification of seized samples based on the purity, chemical form, and the cocaine content. Even though the PLS-DA classification showed rates of true positive between 95 and 97% in separating cocaine with different chemical form and content, the training set samples had only four adulterants and hence limited the models use for unknown samples that contain other adulterants.…”
Section: Introductionmentioning
confidence: 99%
“…Global optimized alignment algorithms are the most dynamic and robust methods of alignment as they maximize a local, as well as a global, measure of similarity [23, 30-A c c e p t e d M a n u s c r i p t 9 32]. In this work, a correlation optimized warping (COW) algorithm was investigated, which optimizes the Pearson product-moment correlation (PPMC) coefficient between a sample and target chromatogram [30].…”
Section: Retention-time Alignment Proceduresmentioning
confidence: 99%
“…[1] Since publication of this report, there has been increasing interest in applying multivariate statistical procedures to forensically relevant chromatographic and spectral data. For example, principal components analysis (PCA), cluster analysis, and discriminant analysis have been applied in the analysis of fire debris [2][3][4][5], explosives [6], controlled substances [7][8][9], and various trace evidence types including hair [10], soil [11], electrical tape [12], and paint [13][14][15]. Forensic research in this area has conclusively demonstrated the potential of these procedures for case work.…”
Section: Introductionmentioning
confidence: 98%